Faktor - Faktor Determinan Kurs Rupiah Terhadap Dollar Amerika - - Utomo; elys fauziyah (MediaTrend, 2017)
Indonesia is a developing country that is often affected by fluctuations in foreign exchange rates, especially US Dollar. This condition is the effect of the government policies that implement the floating exchange rate system since August 14, 1977. The aims of this study are to know the development and to analyze the effect of macroeconomic variables on the Rupiah exchange rate against US Dollar in 2008-2014. The method which used in this study is descriptive statistics and multiple linear regression. The results of the study show that during 2008-2014, the variables of inflation, interest rate (BI rate) of Indonesia’s balance of payments, and exports fluctuated, while the variable of PDB tended to increase. Other results show that interest rates and gross domestic product have a positive effect on the exchange rate of Rupiah against US Dollar, whereas the inflation and exports have a negative effect. Meanwhile, Indonesia’s balance of payments does not significantly affect the Rupiah against US Dollar. Keywords: Exchange Rate, Fluctuation, Macroeconomic Variables